Membangun Industri Kreatif Usaha Umkm Berbasis Literasi Digital Terhadap Peningkatan Ekonomi Pemerintah Kota Tanjungbalai - Ningsi P, Silfira Ayu; Suhairi, Suhairi (Universitas Labuhanbatu, 2022)
Micro, small and medium enterprises (UMKM) in the national economy have an important and strategic role. (UMKM) also have a strategic role in national economic development, therefore in addition to playing a role in economic growth and employment, they also play a role in the distribution of development results. This study aims to build a creative industry for SMEs based on digital literacy to improve the economy of the Tanjungbalai City government. This research is divided into two parts, the first is to find out how the growth of the creative industry MSME business through digital literacy builds the government economy in Tanjungbalai City and the second is to find out how to build a digital literacy-based creative industry MSME business in Tanjungbalai City. This research method is a research with a quantitative approach. Quantitative research is more focused on the use of numbers which makes it more detailed and clearer.Â